Chemical doping of lead-free metal-halide-perovskite related materials for efficient white-light photoluminescence. (February 2023) - Nie, Jingheng; Zhou, Bo; Fang, Shaofan; Wang, Ye; Wang, Yu; Tian, Bingbing; Hu, Hanlin; Zhong, Haizhe; Li, Henan; Shi, Yumeng
Abstract: Metal halide perovskites (MHPs) comprise a vast family of emerging semiconducting with exceptional optoelectronic properties including high photoluminescence quantum yield, long exciton lifetime and tunable light emission wavelength. Owing to these outstanding features, research on the exciton physics of MHP materials is booming, with MHPs having become promising alternatives for high-performance solid-state lighting and display. However, owing to the diverse chemical composition and versatile lattice structure of perovskites, their light-emitting mechanisms remain a big puzzle. Contradictory reports on the light-emitting mechanism can be commonly found in the literature, hence, it is of great necessity and interest to explore the in-depth understanding of the exciton behaviors and fundamental properties in metal halide perovskites. In this review, a critical overview of the different experimental and theoretical approaches applied to determine the exciton emission mechanism is provided. Exciton emission could occur either from the intrinsic perovskite crystals or elemental impurities. However, to date, the problem of the exciton emission mechanism in perovskite crystals with ion impurities has been neglected by most studies. Ion impurities in perovskites materials have been shown to reconcile at least some of the experimental observations in the literature. Furthermore, intentional doping strategies for triggering efficient light emission in MHPs are summarized. The light emission of MHPs can be flexibly engineered via diverse approaches, including the introduction of lone-pair ns 2 cations, the utilization of crystal-field effects, and incorporating new emitting centers. Detailed discussion of the mechanisms underlying the remarkable optical properties from a physics viewpoint is provided, attempting to construct a comprehensive understanding that would be beneficial for the development of efficient light-emitting devices. The diverse chemical composition and strong interaction between dopant and host makes them an ideal application platform for achieving high luminescent efficiency and broadband light emission, which might also provide new concepts and strategies for the design and preparation of perovskite-based optoelectronic materials in future.